2014
DOI: 10.2486/indhealth.2012-0145
|View full text |Cite
|
Sign up to set email alerts
|

Health Impacts of Workplace Heat Exposure: An Epidemiological Review

Abstract: With predicted increasing frequency and intensity of extremely hot weather due to changing climate, workplace heat exposure is presenting an increasing challenge to occupational health and safety. This article aims to review the characteristics of workplace heat exposure in selected relatively high risk occupations, to summarize findings from published studies, and ultimately to provide suggestions for workplace heat exposure reduction, adaptations, and further research directions. All published epidemiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
190
2
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(204 citation statements)
references
References 74 publications
(120 reference statements)
7
190
2
5
Order By: Relevance
“…However, similar to Bai et al [37], we have observed that males have greater risks than females, possibly due to the nature of their work, which mostly entail working outdoors. Outdoor workers, especially those with labor intensive workloads requiring high physical activity under the sun, are vulnerable to heat stress during hot days [38]. In Thailand, construction workers reported suffering from severe heat strain due to the physically strenuous workload [39].…”
Section: Discussionmentioning
confidence: 99%
“…However, similar to Bai et al [37], we have observed that males have greater risks than females, possibly due to the nature of their work, which mostly entail working outdoors. Outdoor workers, especially those with labor intensive workloads requiring high physical activity under the sun, are vulnerable to heat stress during hot days [38]. In Thailand, construction workers reported suffering from severe heat strain due to the physically strenuous workload [39].…”
Section: Discussionmentioning
confidence: 99%
“…First of all, many agricultural activities are performed during the warm season, often requiring the use of personal protective equipment (PPE). As the wearing of PPEs increases physical strain and restricts heat loss from the body, it directly increases the risk for heat-related illness [3,5,22,32], at the same time prompting some workers to reduce their use, ultimately increasing the risk for incidents associated with the use of chemicals, such as pesticides and fertilizers [28]. Secondly, even though the mechanization of many agricultural activities has restrained the strenuous physical labor carried out by AWs, therefore reducing their vulnerability to environmental and exertional heath stress, many farming activities still requires manual work, also in high income countries (e.g., collection of apples and oranges).…”
Section: Materials and Methods Settingsmentioning
confidence: 99%
“…During the last decades, average global surface temperatures have steadily increased, with more hot days and warm nights, fewer cool days and cold nights, and more frequent, hotter and longer heatwaves (HWs) [1][2][3]. Available estimates suggest that the increased magnitude and frequency of extreme events would ultimately lead to a significant excess in morbidity and mortality for cardiovascular and respiratory illnesses, and that the climate changes will presumptively increase both the incidence and the severity of these effects [4][5][6][7][8][9][10][11][12], in particular in Mediterranean-like climates [13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, younger people spend more time on intense activities such as marathons and jogging than the elderly; this could increase their heat load [48]. Younger people may be engaged in physically demanding or outdoor work, for example in agriculture and construction sector, making them more vulnerable to high temperatures [49]. The previous studies also reported that high temperature was associated with a higher risk of work-related injuries [50,51] although the health impact of high temperature has not been fully studied in occupational settings.…”
Section: Discussionmentioning
confidence: 99%